2012
DOI: 10.1021/nn304599d
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Switching of the Interparticle Distance in DNA-Templated Gold Nanoparticle Dimers

Abstract: We produce gold nanoparticle dimers with a surface-to-surface distance that varies reversibly by a factor of 3 when hybridizing or removing a single target DNA strand. The dimers are built on one DNA template that features a stem-loop enabling the interparticle distance change. Using electrophoresis, we reach 90% sample purities and demonstrate that this chemical process is reversible in solution at room temperature for a low molar excess of the target DNA strand. The kinetics of the reaction is asymmetric due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 46 publications
2
80
0
Order By: Relevance
“…106,118 Bidault et al reported reversible switching of inter-particle distances in DNA bridged gold nanoparticle dimers. 119 The distance between gold nanoparticles could be switched from 5 nm to 15 nm, by hybridizing or removing a single DNA strand. A recent report revealed that a 1 nm gap can be generated by DNA-tailored nanoparticles.…”
Section: Electromigration Break Junctions (Ebjs)mentioning
confidence: 99%
“…106,118 Bidault et al reported reversible switching of inter-particle distances in DNA bridged gold nanoparticle dimers. 119 The distance between gold nanoparticles could be switched from 5 nm to 15 nm, by hybridizing or removing a single DNA strand. A recent report revealed that a 1 nm gap can be generated by DNA-tailored nanoparticles.…”
Section: Electromigration Break Junctions (Ebjs)mentioning
confidence: 99%
“…DNA‐based templating approaches allow AuNPs to be precisely positioned in an assembly by Watson–Crick base pairing to provide a tunable interparticle gap . The interparticle distance can be changed by using various chemical reactions of DNA linkers, including cleavage and strand exchange . Despite such steady progress, however, it still remains a challenging task to tune the interparticle distance in single AuNP oligomers in a rapid and reversible way.…”
Section: Introductionmentioning
confidence: 99%
“…One group acknowledged the possibility of drying effects changing the nanostructure of the sample, but there was no investigation on the magnitude of these effects (Elbaz et al, 2013). Cryo-TEM has been applied to these samples for imaging the nanostructure in a hydrated state, though this research did not consider the assembly distortions that can arise during the vitrification process in these samples (Lermusiaux et al, 2012). To image these assemblies in their native state, we utilized a specialized specimen holder that allows a solution to be introduced and sealed between two thin film silica nitride (SiN) membrane windows, maintaining hydration while under vacuum within the microscope column (de Jonge et al, 2009).…”
Section: Introductionmentioning
confidence: 99%